IDENTIFICATION OF HUMAN GRANULOCYTIC ANAPLASMOSIS AND MONOCYTIC EHRLICHIOSIS NATURAL FOCI IN THE KRASNOYARSK TERRITORY - E. K. Doroshchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2013)
Microbiological monitoring of the six districts of the Krasnoyarsk Territory was conducted in order to prove the existence of natural foci of human granulocytic anaplasmosis (HGA) and monocytic ehrlichiosis (HME) on its territory. Two-round PCR method was used for the detection of Anaplasma and Ehrlichia DNA. 374 samples from mites were analyzed with two-round PCR for the presence of Anaplasma and Ehrlichia DNA: 341 specimens of Ixodes persulcatus and 33 specimens of Haemaphysalis concinna. Ticks were collected from vegetation on the flag in the 6 districts of the Krasnoyarsk Territory: Yeniseisky, Achynsky, Sharypovsky, Ilansky, Minusinsky and Ermakovsky, belonging to different climate zones and have landscaped, geo-botanical and faunal features. The study showed that 5.6 % of taiga ticks infected with E. muris, 2,1 % with A. phagocytophilum. In 0.3 % of carriers we identified mixtinfected E. muris and A. phagocytophilum. These data indicate presence of HGA and HME foci in the central, western and southern parts of the Krasnoyarsk Territory.